Integrating transcriptomic and metabolomic analysis to understand natural leaf senescence in sunflower - Moschen, Sebastian; Gonzalez, Sergio Alberto; Rivarola, Maximo Lisandro; Hopp, Horacio Esteban; Paniego, Norma Beatriz; Fernandez, Paula del Carmen; Heinz, Ruth Amelia; Bengoa Luoni, Sofia Ailin; Di Rienzo, Julio A.; Caro, María del Pilar; Tohge, Takayuki; Watanabe, Mutsumi; et al. (2017)
Leaf senescence is a complex process, which has dramatic consequences on crop yield. In sunflower, gap between potential and actual yields reveals the economic impact of senescence. Indeed, sunflower plants are incapable of maintaining their green leaf area over sustained periods. This study characterizes the leaf senescence process in sunflower through a systems biology approach integrating transcriptomic and metabolomic analyses: plants being grown under both glasshouse and field conditions. Our results revealed a correspondence between profile changes detected at the molecular, biochemical and physiological level throughout the progression of leaf senescence measured at different plant developmental stages. Early metabolic changes were detected prior to anthesis and before the onset of the first senescence symptoms, with more pronounced changes observed when physiological and molecular variables were assessed under field conditions. During leaf development, photosynthetic activity and cell growth processes decreased, whereas sucrose, fatty acid, nucleotide and amino acid metabolisms increased. Pathways related to nutrient recycling processes were also up-regulated. Members of the NAC, AP2-EREBP, HB, bZIP and MYB transcription factor families showed high expression levels, and their expression level was highly correlated, suggesting their involvement in sunflower senescence. The results of this study thus contribute to the elucidation of the molecular mechanisms involved in the onset and progression of leaf senescence in sunflower leaves as well as to the identification of candidate genes involved in this process.